High Frequency of False-Positive Hepatitis C Virus Enzyme-Linked Immunosorbent Assay in Rakai, Uganda - Mullis, Caroline E.; Laeyendecker, Oliver; Reynolds, Steven J.; Ocama, Ponsiano; Quinn, Jeffrey; Boaz, Iga; Gray, Ronald H.; Kirk, Gregory D.; Thomas, David L.; Quinn, Thomas C.; Stabinski, Lara (Clinical infectious diseases, 2013)
The prevalence of hepatitis C virus (HCV) infection in sub- Saharan Africa remains unclear. We tested 1000 individuals from Rakai, Uganda, with the Ortho version 3.0 HCV enzyme-linked immunosorbent assay. All serologically positive samples were tested for HCV RNA. Seventy-six of the 1000 (7.6%) participants were HCV antibody positive; none were confirmed by detection of HCV RNA.
Keywords: Hepatitis C virus; ELISA; Africa